Análise de custos : um estudo na produção de soja em propriedade rural de Saldanha Marinho/RS - Teixeira, Guilherme Castelli (2022)
The growth of agribusiness has been standing out in recent times, demanding knowledge of the costs to better manage the rural enterprise. The present study had the general objective of identifying the costs and results involved in the production of soybeans in the 2021/2022 harvest in a rural property of the Muller Family located in Saldanha Marinho/RS. The study methodology is a mixed research (qualitative and quantitative), exploratory and descriptive, contemplating a case study. Data collection was applied through interviews and access to the property management system, after the results were analyzed and compiled, with absorption costing methods to find the result of the temporary culture and variable costing to discover the balance point. The results of the present study show that the Soy culture delivered a profitability of 54.22% of net operating revenue, being able to cover its costs and expenses and deliver the profitability expected by the company. As main recommendations, a more assertive use of the property's control system and the feasibility study of building a dryer silo for grain storage, with the aim of increasing revenue from the sale of the product.